INFLUENCE OF CURRENT REFEREEING RULES ON THE CONTENT OF COMPETITIVE ACTIVITY OF JUDOKAS - Rudenko, G.V.; Izotov, E.A.; Levitsky, A.G.; Avakyan, A.G. (Theory and Practice of Physical Culture, 2023)
Objective of the study was to assess the negative impact of the current competition rules on the content of the competitive activity of judokas. Methods and structure of the study. The object of study is the individual judo tournament among men as part of the 2020 Olympics in Tokyo. Based on the analysis of the competitive activity of judoists, an attempt was made to assess the nature of the existing shortcomings and identify trends in the development of modern judo. The analysis of the protocols of weighing and competitions made it possible to establish the extreme values of the duration of fights and the percentage of judges' marks and punishments in each weight category. Results and conclusions. The vast majority of refereeing decisions account for the punishment of athletes for prohibited actions. 339 shido penalties and 26 hansoku-make disqualifications. Changes are needed in the rules of the competition for the period 2022-2024, aimed at increasing the effectiveness, the growth of entertainment and, due to this, the popularity of judo.